From unbundling to market making: reimagining, reassembling and reinventing the public university. (1st January 2019) - Lewis, Nick; Shore, Cris
ABSTRACT: In Britain and New Zealand the neoliberal assault on universities has shifted from new public management and funding models to the special status of the public university. The project aims to complete neoliberal business initiated 25 years ago by more fully marketising and financialising universities, starting with 'unbundling' and outsourcing and culminating in new forms of privatisation, rent-extraction and rebundling. This paper analyses two documents commissioned beyond government to create political momentum for this project: Avalanche is Coming and The University of the Future . These both capture the zeitgeist of reform while simultaneously creating the university futures that they portend. We examine the market-making work they perform in reimagining and reinventing universities ahead of policy reform. We argue that claims made to support fundamental restructuring of public universities lack substance or evidence. Rather, each is underpinned by different configurations of ideology and self-interest that together envelope universities in new agendas of marketisation, financialisation and privatisation. We suggest that in this latest restructuring of public universities critics should pay more attention to the work of consultancies and think tanks alongside the micro-details of market making. By doing so, they too might reimagine public universities, but for a different political project.